Dynamic rotational alteration in positional relationship of neurovascular structures and distal biceps tendon insertion: a cadaveric study. Issue 6 (16th October 2019) - Bhatia, Deepak; Naskar, Rajib; DeNiese, Pascal
Abstract : Objectives: This study analysed the change in positional relationship of major neurovascular (NV) structures with the distal biceps tendon (DBT) insertion with dynamic rotation. Methods: Fresh frozen cadaveric upper extremities (n=10) were dissected to expose DBT and five major NV structures (ulnar artery (UA), radial artery (RA), median nerve (MN), superficial radial nerve (SRN) and posterior interosseous nerve (PIN)). The distance between each NV structure and the DBT insertion was measured with the elbow in (a) full supination (90°), (b) neutral rotation (0°) and (c) full pronation (80°). Statistical analysis was performed to determine significant changes in rotational NV excursion in relation to DBT insertion. Results: RA and UA were in contact with DBT just distal to the bifurcation of brachial artery. RA was closest to DBT insertion in supination (5 mm), and MN (7 mm) and UA (9 mm) were further away. UA was in close proximity in neutral (4 mm) and pronated (6 mm) positions. UA moved significantly closer to DBT insertion when rotated from supination to neutral (p<0.0001) and pronated (p<0.0018) positions. RA and MN moved significantly further from DBT in these positions (p<0.05). SRN and PIN were the farthest structures from DBT insertion in supination and neutral positions. Conclusion: NV structures in the cubital fossa are in close proximity to DBT and its tuberosity insertion and dynamic rotation significantly changes their positional relation with DBT insertion. Level of evidence: Basic science study